Miguel Verstrasim, Liliana Mannina de Gamero, Maria Rosa Catana, Angélica Gabrielidis de Luna, Armando Rodríguez, El concepto del hombre; exégesis e interpretación del "De Animar de Aristóteles y su proyección contemporánea, Ed. Propedéutica, Mendoza, 1985, 316 págs - García Losada, Matilde Isabel (1987)
Fil: García Losada, Matilde Isabel. Pontificia Universidad Católica Argentina; Argentina